Sintesis Hijau Nanopartikel TiO2 Menggunakan Ekstrak Daun Belimbing Wuluh (Averrhoa blimbi L.) dan Aktivitas Antibakterinya Terhadap Escherichia coli - Nur Azizah Wanda Triyaruhana; Dina Kartika Maharani (Unesa Journal of Chemistry, 2026)
TiO2 nanoparticles were successfully synthesized by biosynthesis method specifically green synthesis method using Averrhoa bilimbi L. (bilimbi) leaf extract as both a reducing and capping agent. The purpose of this study was to characterize the synthesized TiO2 nanoparticles and its antibacterial activity against the Gram-negative bacteria Escherichia coli. Characterization was carried out using Fourier-Transform Infrared Spectroscopy (FTIR) and X-Ray Powder Diffraction (XRD). The synthesized TiO2 nanoparticles exhibited an anatase phase, with an average crystallite size of 12.9 nm and a crystallinity of 97.81%. Antibacterial activity tests against Escherichia coli across various samples Ti-BW20 and Ti-BW40, yielded inhibition zone diameters of 7.82 mm and 9.87 mm, respectively.